Noise exposure of music teachers - Behar, Alberto; MacDonald, Ewen; Lee, Jason; Cui, Richard; Kunov, Hans; Wong, Willy (Canadian Acoustics, 2002)
Measurement of noise exposure levels from single activities (classes) such as rehearsing of bands or teaching a theory was performed. The choice to focus on an activity was made since the ’activity’ was more easily defined than determining a ’typical’ day for music teachers. The physical environment, the number of students involved and activity duration were recorded. Results suggested that hearing protection was needed depending on the schedule of the music teacher.